Climate change, risks and adaptation in the megacity of São Paulo, Brazil - Di Giulio, Gabriela Marques; Bedran-Martins, Ana Maria; Vasconcellos, Maria da Penha; Ribeiro, Wagner Costa (Sustainability in Debate, 2018)
In this paper, we discuss results of a study that sought to investigate the experience of the megacity of São Paulo related to climate issues. Based on the literature review and empirical study conducted between 2014-2015, we shed light on the role of local power in the process of seeking synergies amongst adaptation, mitigation and development throughout experimentation. We discuss some local actions, which have potential to respond to climate challenges, focusing on the interventions that have not been directly associated to climate discourse. Examples of these interventions are the New Master Plan and urban mobility actions adopted by the municipal government (2013-2016). We argue that these strategies and the adoption of a socioenvironmental agenda may be concrete local responses to climate change, connecting synergies between adaptation and mitigation. We conclude exploring some of barriers for local adaptation, taking into account its economic/social/political specificities and complexities.